2021
DOI: 10.1186/s40834-021-00163-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of modern contraceptive use and intention to usecontraceptives among Malawian women of reproductive ages (15–49 years)

Abstract: Background Malawi is one of the countries in SSA with the highest TFR. This study aimed to explore factors associated with modern contraceptive use and intention to use contraceptives among women of reproductive ages (15–49 years) in Malawi. Methods The study used secondary data from 2015 to 16 Malawi Demographic and Health Survey (MDHS) dataset. Logistic regression models were used to derive adjusted odd ratios as the measures of association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
11
15
0
Order By: Relevance
“…The proportion of participants who were intended to use contraceptive in the future was 48.63 (47.42-49.84). This figure is less observed than studies conducted in Indonesia 63%(29), in Ghana 70%(30, 31), in Uganda(32), in Malawi (33), in Ethiopia 84.3% (34) and it is almost in agreement with studies conducted in Ghana 49.3%(35), however this figure is higher than studies investigated in Ethiopia (17, 36). The possible justification why the observed findings of this study is less than the above mentioned one might be due to countries profiles of family planning experience, participants attitude, knowledge and education backgrounds towards family planning intention.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The proportion of participants who were intended to use contraceptive in the future was 48.63 (47.42-49.84). This figure is less observed than studies conducted in Indonesia 63%(29), in Ghana 70%(30, 31), in Uganda(32), in Malawi (33), in Ethiopia 84.3% (34) and it is almost in agreement with studies conducted in Ghana 49.3%(35), however this figure is higher than studies investigated in Ethiopia (17, 36). The possible justification why the observed findings of this study is less than the above mentioned one might be due to countries profiles of family planning experience, participants attitude, knowledge and education backgrounds towards family planning intention.…”
Section: Discussionsupporting
confidence: 50%
“…On the other hand, this study founds significantly higher prevalence of intention to use other studies conducted at various study setting with different times. A study conducted in Cameron (37), in Zambia (38), in Uganda (32), in Malawi (33), and in Ethiopia (39). This is related to the fact that older women may be in less need of contraceptive methods (40).…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of modern contraception among Okun women of reproductive age, on the other hand, is consistent with their low fertility, which may be traced back to Yoruba ethnic group in Southwest Nigeria, suggesting that modern contraceptive use has a cascading effect from this majority ethnic group (14,(32)(33)(34). This is similar to earlier research that has found ethnicity to be a strong predictor of contraceptive use (15,29,30).…”
Section: Discussionsupporting
confidence: 84%
“…In sub-Saharan African countries, there has been evidence of modern contraceptive use differentials among ethnic groups (25)(26)(27)(28)(29)(30). For instance, a study in Malawi showed that Tonga women are less likely to use modern contraceptives than Nyanga women (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation